PATTERNS OF BIOTIC CHANGE IN MIDDLE JURASSIC TO EARLY CRETACEOUS TETHYAN RADIOLARIA - Danelian T.; Johnson K.G. (My University, 2001)
The rate of taxic turnover of nearly 400 radiolarian species/subspecies is analyzed in order to document long term biotic change of plankton during the Middle Jurassic to Early Cretaceous (Aalenian to Aptian). The pattern and dynamic of diversity change is described using four indices: rate of species first and last occurrence, rate of diversification and rate of turnover. Plots of cumulative sampling effort suggest that the analyzed data represent an adequate sample of total standing diversity for most examined stages. Rates of species first occurrence exceed rates of last occurrence for most of the Middle Jurassic, except for the middle Bajocian. In contrast, the Late Jurassic was a time of decreasing radiolarian diversity and the Kimmeridgian records the lowest rate of diversification. It is followed by a dramatic increase in first occurrences near the Jurassic–Cretaceous boundary with as a result the highest rate of diversification recorded in the late Tithonian. Regional radiolarian diversity was stable throughout most of the Early Cretaceous. A stratigraphic permutation test was performed to assess the influence of uneven sampling on the observed pattern of taxic turnover and identified the intervals for which randomly obtained patterns are significantly different from the observed pattern. The Kimmeridgian and late Tithonian events coincide with substantial climate-derived perturbations in water cycling, nutrient supply and oceanic productivity. They point to a negative relationship between radiolarian macroevolution and changes in the state of nutrient availability, although further work is needed to refine the temporal resolution of this relationship and to explore ecological aspects of its causal link with respect to radiolarian evolution.
Keywords: Cretaceous; Jurassic; Radiolaria; Tethys; Mesozoic::Jurassic; Мезозой::Юрская; Мезозой::Меловая; Mesozoic::Cretaceous